2015
DOI: 10.1111/tan.12562
|View full text |Cite
|
Sign up to set email alerts
|

High levels of soluble MICA are significantly related to increased disease‐free and disease‐specific survival in patients with cervical adenocarcinoma

Abstract: Downregulation of major histocompatibility complex class I chain-related molecule A (MICA) and upregulation of human leukocyte antigen G (HLA-G) on the tumor cells are important immune escape mechanisms for different epithelial tumors. In addition, upregulation of the soluble forms of the latter molecules in serum leads to peripheral T-cell and natural killer (NK)-cell tolerance. As for cervical cancer, it remains unknown whether soluble MICA (sMICA) and soluble HLA-G (sHLA-G) concentrations are related to tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…While it is well known that SCC and UCAC present different molecular profiles [32], as well as distinctive pathogenesis and clinical behavior, the current treatment regimens are still relatively the same for both histologically different cervical cancers; these conventionally involve surgery, radiotherapy, and chemotherapy. In line with the above, there is significant evidence that UCAC have a greater propensity to metastasis and have worse prognosis, than SCC [6,33]. Thus, it is feasible to (10x, 20x, 40x, and 63x) from a cervicitis sample.…”
Section: Discussionmentioning
confidence: 66%
“…While it is well known that SCC and UCAC present different molecular profiles [32], as well as distinctive pathogenesis and clinical behavior, the current treatment regimens are still relatively the same for both histologically different cervical cancers; these conventionally involve surgery, radiotherapy, and chemotherapy. In line with the above, there is significant evidence that UCAC have a greater propensity to metastasis and have worse prognosis, than SCC [6,33]. Thus, it is feasible to (10x, 20x, 40x, and 63x) from a cervicitis sample.…”
Section: Discussionmentioning
confidence: 66%
“…32 Indeed, previous studies showed that peripheral blood monocytes are the predominant cells secreting HLA-G5. 33 In this study, the relatively large number of CRC patients included in our evaluation (n 5 133) allowed for investigation of the prognostic value of plasma sHLA-G. Several clinical studies found no correlation between sHLA-G concentration in plasma/serum and clinical parameters including overall survival and disease free survival in cervical cancer, 34 esophageal squamous cell carcinoma 35 and melanoma patients. 33 On the other hand, in non-small-cell lung cancer patients with squamous cell carcinoma it was shown that high levels of sHLA-G is significantly associated with shorter overall survival.…”
Section: Discussionmentioning
confidence: 92%
“… 1 , 2 Several types of cervical tumor histology can be distinguished, but the most commonly applied stratification is squamous cell carcinoma vs adenocarcinoma, both with different oncogenic mutations, 3 , 4 and different immunological tumor microenvironment. 5 , 6 , 7 Despite these substantial differences, current treatment modalities are the same for both squamous cell carcinomas and adenocarcinomas. 8 At present, patients with cervical cancer are treated with radical hysterectomy and pelvic lymphadenectomy or chemoradiation, depending on tumor stage and tumor size.…”
mentioning
confidence: 99%